Efektifitas Pemberian Aromaterapi Lavender dan Relaksasi Benson terhadap Penurunan Skala Nyeri Pasien Fraktur di Ruang Bedah RSUD Prof. Dr. H. Aloei Saboe - Agnes Doki; Fadli Syamsuddin; Sabirin B. Syukur; Siti Qomaria Usu (Lembaga Pengembangan Kinerja Dosen, 2026)
Introduction: Pain in fracture patients is a major problem that often occurs and can disrupt the physical and psychological condition of the patient. Pain management generally uses pharmacological therapy, but can cause side effects if used long-term. Therefore, non-pharmacological interventions such as lavender aromatherapy and Benson relaxation are needed, which are considered safe, easy to implement, and effective in reducing pain intensity and increasing patient comfort during treatment. Methods: This study used a quantitative method with a pre-experimental design through a pretest-posttest approach. A sample of 30 respondents was selected using a purposive sampling technique. Respondents were divided into two intervention groups, namely lavender aromatherapy and Benson relaxation. Pain scale measurements were carried out using the Numeric Rating Scale (NRS). Data analysis was carried out using the Wilcoxon Signed Rank Test to determine differences before and after the intervention. Results: The results showed that before the intervention, most respondents experienced severe pain. After the intervention, there was a decrease in the pain scale to moderate pain in both groups. The significance value for the lavender aromatherapy group was p = 0.001 and for the Benson relaxation group p = 0.000, indicating a significant effect on pain reduction. The average pain reduction in the lavender aromatherapy group was 2.67, while in the Benson relaxation group it was 2.80. Discussion: Lavender aromatherapy and Benson relaxation have been shown to be effective in reducing pain scales in fracture patients. Benson relaxation showed slightly superior results because it was able to provide a deeper relaxation effect through breathing regulation and the body's physiological responses. These two interventions can be alternatives in non-pharmacological pain management and support improving the quality of nursing care.